What Makes a "Leading" Case - Richardson, Sir Ivor (Victoria University of Wellington Law Review, 2010)
The theme developed in the paper is that what makes a leading case is not immediately apparent or able to be captured in a short definition. The crucial questions are how and why a case is seen to be or to have been particularly influential in settling an area of the law. Exploring these questions necessarily involves viewing the case in its historical context. Economic and behavioural implications and impacts should also be kept in mind. The paper draws on empirical research involving retired judges, experienced lawyers and judges' clerks and on specialist essays by senior academic lawyers produced for the 50th anniversary conference of the Court of Appeal in 2008. The research results show how much room there is for differing assessments of significance. The second half of the paper discusses a range of appeal cases explaining how and why the Court focussed on particular matters of significance in deciding the cases.